Crystal structure of bromidobis(naphthalen- 1-yl)antimony(III) - Shawkataly, Omar; Hussien Abdelnasir, Hafiz Malik; Rosli, Mohd Mustaqim (International Union of Crystallography, 2014)
In the title compound, [SbBr(C10H7)2], the SbIII atom has a distorted trigonal–pyramidal coordination geometry and the planes of the two naphthalene ring systems make a dihedral angle of 80.26 (18). An intramolecular C—H Br hydrogen bond forms an S(5) ring motif. In the crystal, weak C—H Br interactions link the molecules into helical chains along the baxis direction.